2024
DOI: 10.3389/fendo.2024.1325434
|View full text |Cite
|
Sign up to set email alerts
|

The role of machine learning in advancing diabetic foot: a review

Huifang Guan,
Ying Wang,
Ping Niu
et al.

Abstract: BackgroundDiabetic foot complications impose a significant strain on healthcare systems worldwide, acting as a principal cause of morbidity and mortality in individuals with diabetes mellitus. While traditional methods in diagnosing and treating these conditions have faced limitations, the emergence of Machine Learning (ML) technologies heralds a new era, offering the promise of revolutionizing diabetic foot care through enhanced precision and tailored treatment strategies.ObjectiveThis review aims to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Clinicians can now utilize biomarkers for early diagnosis of DFU to initiate timely interventions ( Wang et al, 2021 ; Li Y. et al, 2022 ; Shi et al, 2023 ; Shi et al, 2024 ). It has been previously shown that the integration of bioinformatics and machine learning has become an important tool for identifying novel biomarkers associated with DFU ( Khandakar et al, 2021 ; Chemello et al, 2022 ; Guan et al, 2024 ; Hettinger et al, 2024 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians can now utilize biomarkers for early diagnosis of DFU to initiate timely interventions ( Wang et al, 2021 ; Li Y. et al, 2022 ; Shi et al, 2023 ; Shi et al, 2024 ). It has been previously shown that the integration of bioinformatics and machine learning has become an important tool for identifying novel biomarkers associated with DFU ( Khandakar et al, 2021 ; Chemello et al, 2022 ; Guan et al, 2024 ; Hettinger et al, 2024 ).…”
Section: Introductionmentioning
confidence: 99%